Cellular Reprogramming Allows Generation of Autologous Hematopoietic Progenitors From AML Patients That Are Devoid of Patient‐Specific Genomic Aberrations. (21st May 2015) - Salci, Kyle R.; Lee, Jong‐Hee; Laronde, Sarah; Dingwall, Steve; Kushwah, Rahul; Fiebig‐Comyn, Aline; Leber, Brian; Foley, Ronan; Dal Cin, Arianna; Bhatia, Mickie
Abstract: Current treatments that use hematopoietic progenitor cell (HPC) transplantation in acute myeloid leukemia (AML) patients substantially reduce the risk of relapse, but are limited by the availability of immune compatible healthy HPCs. Although cellular reprogramming has the potential to provide a novel autologous source of HPCs for transplantation, the applicability of this technology toward the derivation of healthy autologous hematopoietic cells devoid of patient‐specific leukemic aberrations from AML patients must first be evaluated. Here, we report the generation of human AML patient‐specific hematopoietic progenitors that are capable of normal in vitro differentiation to myeloid lineages and are devoid of leukemia‐associated aberration found in matched patient bone marrow. Skin fibroblasts were obtained from AML patients whose leukemic cells possessed a distinct, leukemia‐associated aberration, and used to create AML patient‐specific induced pluripotent stem cells (iPSCs). Through hematopoietic differentiation of AML patient iPSCs, coupled with cytogenetic interrogation, we reveal that AML patient‐specific HPCs possess normal progenitor capacity and are devoid of leukemia‐associated mutations. Importantly, in rare patient skin samples that give rise to mosaic fibroblast cultures that continue to carry leukemia‐associated mutations; healthy hematopoietic progenitors can also be generated via reprogramming selection. Our findings provide the proof of principle that cellular reprogramming can be applied on a personalized basis to generate healthy HPCs from AML patients, and should further motivate advances toward creating transplantable hematopoietic stem cells for autologous AML therapy. Stem Cells 2013;33:1839–1849